EMISI FORMALDEHIDA DARI PAPAN LANTAI LAMINA KOMBINASI DENGAN BATANG KELAPA YANG MENGGUNAKAN TANIN RESORSINOL FORMALDEHIDA - Supriyono Eko Wardoyo; Adi Santoso; Sri Wuryani Sugiarti (JURNAL SAINS NATURAL, 2011)
Formaldehyde Emissions from Floor Boards Lamina Combination with The Coconut Bar Using Tanin Resorcinol Formaldehyde          Trunks of coconut (Cocos nucifera L.) has been widely used as both structural and non structural materials, including home furnishings, furniture, toys, crates, and so on. In the utilization of coconut trunks required special handling to produce a high quality product. How to handle it needs through the process of densification or impregnation by using a copolymer of Tanin Resorcinol Formaldehyde (TRF) in  the vacuum press. In the case to reduce the scarcity of the wood,  modification between coconut wood with other wood species in laminated floor board products is needed. The research was done by the method of vacuum press in the Laboratory for Products Compound and Wood Preservation, Center Research and Development for Forest Products, Bogor. The tests were performed the  physical properties consist of specific gravity and moisture content or  the chemical properties of formaldehyde emissions by using Spectrophotometer. The results indicated that by using TRF copolymer (1: 0.5: 2) and viscosity 0.88 centripoise, formaldehyde emissions of the combination of the wood was very well and meet the requirements ( 0.30 to 0.40 mg / L) and were included in the category of very safe.Keywords : Emissions of formaldehyde, Laminated boards, Trunks of coconut, Tanin resorcinol formaldehyde ABSTRAK             Batang kelapa (Cocos nucifera L.) telah banyak digunakan baik sebagai bahan struktural maupun non structural, seperti perkakas rumah tangga, mebel, mainan, peti dan lain sebagainya.  Dalam pemanfaatannya batang kelapa tersebut diperlakukan penanganan khusus untuk menghasilkan suatu produk yang berkualitas tinggi. Adapun cara penanganannya adalah dapat melalui proses densifikasi ataupun impregnaasi dengan menggunakan suatu kopolimer  Tanin Resorsinol Formaldehida  menggunakan metode vakum tekan.  Dalam hal ini untuk mengurangi  kelangkaan dari kayu tersebut maka    dilakukan modifikasi antara kayu kelapa dengan jenis kayu lainnya pada produk papan lantai lamina. Untuk itu dilakukan penelitian pengujian dengan metode vakum tekan di Laboratorium Produk Majemuk dan Pengawetan Kayu, Pusat Penelitian dan Pengembangan Hasil Hutan, Bogor . Adapun pengujian yang dilakukan adalah sifat fisika terdiri atas bobot jenis, kadar air, dan  sifat kimia  emisi formaldehida yang diuji dengan menggunakan Spectrophotometer. Hasil penelitian ini menunjukan bahwa dengan menggunakan kopolimer TRF  (1 : 0,5 : 2) dengan kekentalan 0,88 centripoise, emisi formaldehida yang  dihasilkan dari kombinasi kayu tersebut sangat baik dan memenuhi persyaratan   (0,30 - 0,40 mg/L) dan termasuk dalam kategori sangat aman.Kata kunci : Emisi formaldehida, Papan lamina, Batang kelapa, Tanin resorsinol formaldehida